Development of Pancasila Education Learning Module Indonesian Cultural Diversity Material Based on Sintuvu Local Wisdom in Class V SDN 7 Rio Pakava - Uswatun Hasanah; Arif Firmansyah; Muchdar Muchdar; Rizal Rizal; Mas'adi Mas'adi (Journal of Educational Sciences, 2026)
This study aims to develop a Pancasila Education teaching module on Indonesian Cultural Diversity based on Sintuvu local wisdom for fifth-grade students at SDN 7 Rio Pakava. The novelty of this study lies in integrating Sintuvu local wisdom values, including mutual cooperation, togetherness, unity, and social responsibility, into Pancasila Education as a contextual and culture-based learning innovation. This integration is expected to help students understand Indonesian cultural diversity through experiences closely related to their daily lives while strengthening character development based on Pancasila values. This research employed the Research and Development (R&D) method using the Four-D (4D) model, which consists of the define, design, and develop stages, while the disseminate stage was not conducted. The developed module was validated by material and media experts and tested for readability by one teacher and 16 fifth-grade students. The material and media expert validations each obtained an average score of 4.00, categorized as very valid. The teacher readability test achieved an average score of 3.95 (very valid), while the student readability test obtained an average score of 3.22 (valid). These findings indicate that the developed teaching module meets validity criteria and is suitable for use in supporting contextual Pancasila Education learning and strengthening students’ understanding of local wisdom and Pancasila values.